Collapse analysis of slender masonry barrel vaults. (15th June 2016) - Ramaglia, G.; Lignola, G.P.; Prota, A.
Highlights: Some slender masonry vaults require a tensile strength even under gravity loads. Model reliably estimates hinge locations at failure and ultimate load multiplier. Closed form solution for elastic, cracking or plastic behaviours with tensile strength. Analytical model can be graphical too; providing a fictitious geometry for the arch. Validation: shaking table tests on full scale slender masonry vaults with/out backfill. Abstract: Significant part of the world cultural heritage is represented by masonry buildings. Many of them are characterised by a complex architecture like as the religious buildings and need to be preserved, from a structural point of view, especially in high seismic risk areas. The recent earthquakes showed that the Historical and Monumental buildings are often characterised by high seismic vulnerability. The lowest seismic performances are associated with the presence of thrusting elements like as arches and vaults. In this background, the numerical analyses and experimental simulations provide important information about the structural behaviour of such elements. The structural behaviour of curved elements can be complex to simulate and to predict exclusively by numerical analyses. Indeed, the experimental tests can provide an efficient contribution to the calibration and interpretation of the numerical models. The present work focuses on a particular typology of vaults generally used as roofs in religious buildings. These vaults typically do not include any backfill and are slender. These typologies of masonry vaults cannot be analysed with classical approaches where no-tension is assumed. In fact, the tensile strength must be included in order to assess the seismic capacity of these masonry elements. A simplified analytical model, which includes the tensile strength, was proposed. Validation of the analytical model is provided by comparing predictions of the load capacity and the failure mode with those obtained from previous shaking table test series on two full scale masonry vaults. The proposed method represents a useful modelling tool in order to design dynamic tests on masonry vaults and to assess their vulnerability.